Slavenības fenomens populārajā kultūrā: Holivudas aktrise Merilina Monro. Filmu "Some Like It Hot", "Gentlemen Prefer Blondes", "How to Marry a Millionaire" un "Seven Year Itch" analīze - Strupka, Zelma (Latvijas Universitāte, 2012)
Bakalaura darbā tēma ir „Slavenības fenomens populārajā kultūrā: Holivudas aktrise Merilina Monro. Filmu "Some Like It Hot", "Gentlemen Prefer Blondes", "How to Marry a Millionaire" and "Seven Year Itch" analīze”. Darba pētnieciskā problēma ir Merilinas Monro slavas fenomena un viņas tēla nozīmes noteikšana populārajā kultūrā. Teorijā apskatīta akadēmiskā literatūra par populāro kultūru, Holivudu, slavenībām un Merilinu Monro. Metodoloģijā apskatītas metodes: kvalitatīvā kontentanalīze un daļēji strukturētās intervijas. Empīriskajā daļā veikta septiņu dokumentālo filmu kvalitatīvā kontentanalīze, kuras rezultāti salīdzināti ar intervijās iegūtajiem ekspertu viedokļiem. Pielikumā iztirzāts Monro tēls mākslas filmās. Atslēgas vārdi: Merilina Monro, populārā kultūra, slavenības, tēls, kvalitatīvā kontentanalīze, intervijas, dokumentālās filmas

The subject of the bachelor thesis is „The phenomenon of a celebrity in popular culture: Hollywood actress Marilyn Monroe. The study of "Some Like It Hot", "Gentlemen Prefer Blondes", "How to Marry a Millionaire" and "Seven Year Itch"”. The research problem is defining the importance of the phenomenon of Marilyn Monroe’s fame and her image. Theoretical approach is based on the study of popular culture, celebrities and academic literature on Marilyn Monroe. Methodology used – qualitative contentanalysis and partly structured interviews. Research is conducted by using qualitative content analysis on seven documentaries, results are compared with experts’ opinions from the interviews. The image of Monro is analyzed in appendix. Key words: Marilyn Monroe, popular culture, celebrities, image, qualitative content analysis, interviews, documentaries
The phenomenon of a celebrity in popular culture: Hollywood actress Marilyn Monroe. The study of "Some Like It Hot", "Gentlemen Prefer Blondes", "How to Marry a Millionaire" and "Seven Year Itch"
Keywords: Komunikācijas zinātne